Implementasi CSR Perusahaan Kawasan Industri Kimia PT. Chandra Asri Petrochemical.Tbk Di Kecamatan Ciwandan , Kota Cilegon - Sutisna, Nuril Anwar; Suryasuciramdhan, Arfian; Mujahidin, M Halwin; Zulfikar, Meiby; Fatchurrochman, Agus (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The emergence of gas through chimneys in Cilegon City, especially in the Ciwandan Area, has driven social, social and monetary transformation. The rapidly growing industry has changed the social and monetary order of an area that has been recognized as an agrarian culture into a modern culture. The existence of large organizations that utilize natural resources in Ciwandan has increased the hopes of the surrounding community for an increase in wages, through the Corporate Social Obligation (CSR) program. Therefore, the examination tries to uncover elements of CSR implementation in the PT. Chandra Asri area. This investigation is driven by interpretation techniques with emotional thinking as a context-oriented examination. Data collection is carried out through hierarchy collection, integrated discussions, and documentation studies. Meanwhile, the sources of the research include pioneers of the city corridor, city and regional government officials, pioneers in the areas around the current area, and CSR implementers of PT. Chandra Asri, The results of the examination show that CSR training has been carried out by PT for some time. Chandra Asri at least when he was still under joint administration with medical staff, especially those related to assistance in the field of government, including health, education, social and activities in the field of government. The desperation of this examination gave rise to problems that occurred at PT. Chandra Asri, will be fully responsible for things that hinder the environmental climate. Because after air pollution by these substances occurs, its occupants experience diseases such as shortness of breath, weakness, stability and disease. The purpose of this study, researchers can understand and know the response of PT. Chandra Asri, to the surrounding community affected by chemicals and gas leaks carried out by PT. Chandra Asri.